Exploring disulfiram mechanisms in renal fibrosis: insights from biological data and computational approaches - Patil, Vishal S.; Patil, Chandragouda R.; Patel, Harun M.; Kumar, Anoop (Frontiers in Pharmacology, 2025)
BackgroundDisulfiram (DSF) is an anti-alcoholic drug that has been reported to inhibit the epithelial-to-mesenchymal transition and crosslinking during fibrosis, pyroptosis, and inflammatory NF-κB and Nrf-2 signaling pathways. However, there is insufficient evidence to support the mechanisms of DSF in preventing renal fibrosis (RF). Therefore, the current study aimed to elucidate the DSF-modulated targets and pathways in renal fibrosis.MethodsThe common proteins between DSF and RF were screened for protein–protein interaction, pathway enrichment, cluster, and gene ontology analysis. Molecular docking was executed for core genes using AutoDock Vina through the POAP pipeline. Molecular dynamics (MD) simulation (100 ns) was performed to infer protein–ligand stability, and conformational changes were analyzed by free energy landscape (FEL).ResultsA total of 78 targets were found to be common between DSF and RF, of which NFKB, PIK3CA/R1, MTOR, PTGS2, and MMP9 were the core genes. PI3K-Akt signaling followed by JAK-STAT, TNF, Ras, ErbB, p53, phospholipase D, mTOR, IL-17, NF-κB, AMPK, VEGF, and MAPK signaling pathways were modulated by DSF in RF. DSF showed a direct binding affinity with active site residues of core genes, and except for DSF with NF-κB, all other complexes, including the standard, were found to be stable during 100 ns MD simulation with minimal protein–ligand root mean squared deviation and residual fluctuations and higher compactness with broad conformational changes.ConclusionDSF protects against renal fibrosis, and this study paves the way for experimental investigation to repurpose DSF for treating RF.